Prenatal diagnosis of mosaicism for a distal 5p deletion in a single colony at amniocentesis in a pregnancy with a favorable outcome and a review of mosaic distal 5p deletion - Chih-Ping Chen; Liang-Kai Wang; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Wen-Lin Chen; Wayseen Wang (Elsevier, 2020)
Objective: We present prenatal diagnosis of mosaicism for a distal 5p deletion in a single colony at amniocentesis with a favorable outcome, and we review the literature of mosaic distal 5p deletion. Case Report: A 35-year-old primigravid woman underwent amniocentesis at 18 weeks of gestation because of advanced maternal age. Amniocentesis revealed the result of 46,XY,del(5)(p13)[1]/46,XY[19]. Among 20 colonies of cultured amniocytes, all four cells in one colony had a karyotype of 46,XY,del(5)(p13) with a distal deletion of 5p13→pter, while the rest 19 colonies had a karyotype of 46,XY. Repeat amniocentesis was performed at 21 weeks of gestation. Conventional cytogenetic analysis revealed a karyotype of 46,XY in all 20 colonies. Simultaneous array comparative genomic hybridization (aCGH) using the DNA extracted from the uncultured amniocytes revealed no genomic imbalance. Prenatal ultrasound findings were unremarkable. At 38 weeks of gestation, a 3621-g male baby was delivered with no phenotypic abnormality. The cord blood had a karyotype of 46,XY. Postnatal urinary cells analysis by interphase fluorescence in situ hybridization (FISH) using a 5p terminal FISH probe detected no abnormal cell in the urine. Conclusion: Mosaicism for a distal 5p deletion in a single colony at amniocentesis can be associated with a favorable outcome. Keywords: Amniocentesis, Distal 5p deletion, Mosaicism